Pluralism Lost? Defending Hybridism About Being - (:unkn) unknown (My University, 2024)
Ontological Pluralism (OP) is the view that there are restricted existential quantifiers that are at least as natural as the unrestricted existential quantifier. One important question regarding OP that has not received much attention is whether these elite restricted existential quantifiers will be more natural than the unrestricted existential quantifier. In this paper, I defend Hybridism, which is the view that both the unrestricted quantifier and restricted quantifiers are equally natural, from two objections: one relating to its cost in parsimony and the other relating to issues of quantification over certain kinds of entities.